Chemical weathering and atmospheric/soil CO2 uptake in the Andean and Foreland Amazon basins - Moquet, J.S. (2011)
This study is a geochemical investigation of the Andean and Foreland basins of the Amazon River at high spatial and time resolution, carried out within the framework of the HYBAM research program (Hydro-geodynamics of the Amazon Basin). Monthly sampling was carried out at 27 gauging stations located in the upper tributaries of the Amazon Basin (from north to south: the Napo, Marañon, Ucayali, Madre de Dios-Beni and Mamore Rivers). The aim of this paper is to estimate the present-day chemical weathering rate (CWR), as well as the flux of CO2 consumption from total and silicate weathering in the Andes and Foreland Amazon basins, and to discuss their distribution as a function of geomorphic and structural parameters. Based on the forward method, the Napo and other Ecuadorian basins present high silicate weathering rates in comparison with the other basins. We confirm that the Marañon and Ucayali Rivers control the Amazon hydrochemistry due to the presence of salt rocks and carbonates in these basins. The Madre de Dios, Beni and Mamore basins do not contribute much to the Amazon dissolved load. This north to south CWR gradient can be explained by the combination of decreasing weatherable lithology surface and decreasing runoff rates from the north to the south. The foreland part of the basins (or Mountain-Lowland transition) accounts for nearly the same proportion of the Amazon silicate chemical weathering and carbonate chemical weathering fluxes as the Andean part. This result demonstrates the importance of the sediment accumulation areas in the Amazon Basin weathering budget and can be explained by the occurrence of a higher temperature, the deposition of fresh sediments from Andean erosion and a higher sediment residence time than in the upper part of the basin. With a total CO2 consumption rate of 744.103moleskm-2year-1 and a silicate CO2 consumption rate of 300.103moleskm-2year-1, the Upper Amazon River (Andes+Foreland part) is the most intense part of the Amazon Basin in terms of atmospheric CO2 consumption by weathering processes. It is an important CO2 sink by weathering processes but accounts for only somewhat more than half of the CO2 consumption by silicate weathering of the Amazon Basin. This result points out the importance of the Lowland part of the basin in the inorganic C silicate budget. The Upper Amazon accounts for 2-4% of the world's silicate CO2 consumption, which is the same proportion as for the southern and southern-east Himalaya and Tibetan plateau.